Variability and progression in competitive performance of Paralympic swimmers - Fulton, S. K.; Pyne, D. B.; Hopkins, W. G.; Burkett, B. (Journal of Sports Sciences, 2009)
Analysis of variability and progression in performance of top athletes between competitions provides information about performance targets that is useful for athletes, practitioners, and researchers. In this study, 724 official finals times were analysed for 120 male and 122 female Paralympic swimmers in the 100-m freestyle event at 15 national and international competitions between 2004 and 2006. Separate analyses were performed for males and females in each of four Paralympic subgroups: S2-S4, S5-S7, S8-S10 (most through least physically impaired), and S11-S13 (most through least visually impaired). Mixed modelling of log-transformed times, with adjustment for mean competition times, was used to estimate variability and progression. Within-swimmer race-to-race variability, expressed as a coefficient of variation, ranged from 1.2% (male S5-S7) to 3.7% (male S2-S4). Swimming performance progressed by approximately 0.5% per year for males and females. Typical variation in mean performance time between competitions was ~1% after adjustment for the ability of the athletes in each competition, and the Paralympic Games was the fastest competition. Thus, taking into account variability, progression, and level of competition, Paralympic swimmers who want to increase substantially their medal prospects should aim for an annual improvement of at least 1-2%.